Ultra‐mutated colorectal cancer patients with POLE driver mutations exhibit distinct clinical patterns. (30th October 2020) - Hu, Hanguang; Cai, Wen; Wu, Dehao; Hu, Wangxiong; Dong Wang, Li; Mao, Jianshan; Zheng, Shu; Ge, Weiting
Abstract: POLE mutations, which lead to an ultramutated phenotype in colorectal cancer (CRC), have been reported as a promising marker in immunotherapy. We performed sequencing of CRC cases in Zhejiang University (ZJU) and extracted obtainable data from recently published results, including The Cancer Genome Atlas (TCGA), Japanese studies and clinical trials, to present clinical patterns of POLE driver‐mutated CRC and reveal its heterogeneity. The rate of somatic POLE driver mutations has been reported as 2.60% (ZJU cohort), 1.50% (TCGA cohort), 1.00% (Japan cohort), and 1.00% (Lancet cohort). POLE driver mutations show a clearly increased mutation burden (mean TMB: 217.98 mut/Mb in ZJU; 203.13 mut/Mb in TCGA). Based on pooled data, more than 70.00% of patients with POLE driver mutations were diagnosed before they were 55 years old and at an early disease stage (Stage 0–II >70.00%), and more than 70.00% were male. Among Asian patients, 68.40% developed POLE driver mutations in the left‐side colon, whereas 64.00% of non‐Asian patients developed them in the right‐side colon ( p  < 0.01). The top three amino acid changes due to POLE driver mutations are P286R, V411L, and S459F. Investigators and physicians should ascertain the heterogeneity and clinical patterns of POLE driver mutations to be better equipped to design clinical trials and analyze the data. Abstract : POLE could be a promising marker for immunotherapy, and its heterogeneity should not be ignored. Here we present the clinical patterns and heterogeneity of POLE driver mutations so that investigators and physicians will be better equipped to design clinical trials and analyze their data.